Health and Economy: A Necessary Relationship to Face the Path Towards Sustainable Development in Latin America and the Caribbean, Post-covid - Morales-Molina, Tania (2024)
The health–economy relationship has recently emerged as one of the top priorities at the international level, and the emergence of the virus has caused a lot of human and economic pain. The pandemic has brought human and economic suffering to the international community. Most countries have been affected, and this has been evidenced in the deterioration of health and the contraction of economies, with greater incidence in Latin America and the Caribbean. The main objective was to highlight the current situation of both sectors and possible future developments. The methodology used was a quantitative–descriptive type of scientific research with updated bibliographic information, using as instruments secondary source documents such as state economic reports, updated statistical data, relevant scientific articles and publications in public institutions. The results reflect a difficult health and economic panorama due to internal and external causes, favouring the increase of inequality, poverty and political corruption. The conclusions demonstrate the little evolution that has existed in Latin America and the Caribbean (LAC) post-pandemic in the health sector and in the economy, which was on the verge of total bankruptcy in the face of such a devastating scenario of the coronavirus, with losses of -7.0% of GDP at the American level. Although new variants of the virus appeared and there was a relapse, by the end of the same year, the real GDP was predicted to increase by 6.3% in 2021, to moderate to 3% in 2022, taking into account the reopening of tourism as one of the main sources of income of these countries with 15.5% of the gross domestic product, all in terms of growth and sustainable development.